Bioaccumulation kinetics of copper in Ruditapes philippinarum exposed to increasing, continuous and pulsed exposure: Implications for growth - Santana, Lígia M.B.M.; Blasco, Julián; Abessa, Denis M.S. [UNESP]; Campana, Olivia (Elsevier, 2017)
Metal bioaccumulation and toxicity to aquatic organisms depends on factors such as magnitude, duration and frequency of the exposure. The type of the exposure affects the toxicokinetic processes in the organisms. In this study, we carried out 30-day toxicity tests on juveniles of Ruditapes philippinarum exposed to increasing, continuous and pulsed exposure. Organisms were exposed to copper-spiked sediments followed by a 10-day recovery period. We assessed the interaction between the kinetics of subcellular copper partitioning and the growth response. Results showed that the growth rate of the bivalve was inversely correlated to the bioaccumulation rate and that sublethal copper concentrations stimulated the detoxification mechanisms inside the organism regardless the type of the exposure. However, a large stimulatory effect on growth was observed during the recovery period, associated with significant negative accumulation rate values and dependent on the type of antecedent exposure. This suggested that on individual and short-term basis pulsed exposures have a more adverse effect compared to increasing or continuous exposure scenarios.
Keywords: Bioaccumulation kinetics; Copper; Growth; Ruditapes philippinarum; Sediment